Strategi Peningkatan Loyalitas Nasabah BMT - Abdul Qodir; Ririn Indah Lestari (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2020)
Very tight competition in the financial industry, making financial institutions especially Baitul Mal wa Tamwil must manage their institutions in such a way as possible. One of them is by way of promotion, this is considered effective enough to inform also attract the attention of the public. However, one of the elements and also the spearhead of the success of a product is by promotion. Bmt Syahida Ikaluin in its promotion strategy besides using media also utilizes one of its products namely shahida savings products, this product is a superior product because many members who are members of BMT are part of shahida savings product members. The method used is analytical descriptive using a qualitative approach, while the purpose of this paper is to find out what strategies are used by BMT SYAHIDA IKALUIN in increasing customers through shahida savings products. While the results of this study conclude that the analysis and segmentation of community needs in releasing products that can meet their needs as an opportunity to increase BMT members.